The Ceramics of Singkawang: Dayak Kanayatn’s Cultural Perceptions in Kalimantan Barat - Iwan Pranoto; Vitta Diana Siahaan; Triyanto Triyanto; Tjetjep Rohendi Rohidi (Mudra Jurnal Seni Budaya, 2020)
This study examines the cultural perceptions of Dayak Kanayatn community on Singkawang ceramics. The scope of the problem includes, aesthetic, community perception, and ceramics function based on cultural perception. The research location was in Sebetuk, Antan Rayan Village, Ngabang District, Landak Regency, Kalimantan Barat. A qualitative design in the form of case studies was used. Data were gathered using observation, interviews, and documents. The findings of this study overall proved that Singkawang ceramics owned by Dayak Kanayatn community influenced by Chinese culture as seen on boko’o, siam, jampa, tajau, karokot, siton, twakag ba’butuh, banyanyi, karere, balangkas, oncok tabu, plate variants, tetek ijo. Dayak Kanayatn community believe on ceramics as an incarnation of the ancestors and referred as a tangah symbolized by the variety of decoration and form. The ceramics are used by the community as media for several activities as well on law regulations and are considered as a link between humans and ancestral spirits of the Dayak Kanayatn tribe.